The Influence of Student Understanding of the Use of Bank and Non-Bank Sharia Financial Services (Case Study of Bandung Islamic University Students) - Akhmad Nur Zaroni; Norvadewi Norvadewi; Risa Mayasari (Pusat Riset dan Inovasi Nasional, 2023)
The third National Financial Literacy and Inclusion Survey (SNLIK) conducted by the Service Authority Finance (OJK) in 2022 shows the financial literacy index reaches 38.03%. This figure has increased compared to the results of the 2016 OJK Survey, namely the financial literacy index 29.7%. Thus in the last 6 years there has been an increase in financial understanding (literacy) of the community at 8.33%, SNLIK 2022 also records the level of financial literacy sharia increased slightly from 8.1% to 8.93%. Completing the Survey conducted by OJK, Index Literacy Economy Sharia Year 2022 Which issued by BI reach 16.3% (well literate) from scale 100% Which reflect exists room for effort increase public understanding of Islamic Economics in the country. This research aims to determine the effect of student understanding of the use of Islamic financial services banks and non-banks. The method used in this study is the research method descriptive quantitative. Results study This results testing validity variable understanding is known r count > r table (0.213) with mark significance (p values) < 0.05 so data variable understanding declared valid. Furthermore, the variable of using bank services is obtained r count > r table (0.213) with a significance value (p value) <0.05 so all statement items declared valid. Next, it is known that the calculated t value is 5.417 > t table (1.9904), with a value of probability of 0.000 means less than 0.05 then Ha is accepted, meaning understanding student influential positive significant to use service finance sharia bank And nonbank. As well as obtained coefficient determination (R Square) as big 0.271, It means as big 27.1% of student understanding is able to explain or influence the use of services bank and non-bank sharia finance, while the remaining 72.9% is influenced by factors other which is not researched on research This.